The influence of motivations and environment on business start-ups: Some hints for public policies - Dubini, Paola (Journal of Business Venturing, 1989)
This paper examines entrepreneurial motivations to start a business in different perceived environmental settings. Motivations to start a business for a sample of 163 entrepreneurs (from growing and declining regions in the north, center and south of Italy) were factor-analysed in order to identify the main groupings of variables that lead people to start their own business. The results proved to be highly consistent with Friberg's (1975, 1976) findings on incentives to start a business. The motivation factor scores were then clustered, and three verv different classes of entrepreneurs were identified, each driven by very different sets of motivations: self actualizers who started their business driven by a thirst for achievement and a sense of independence and autonomy; discontented entrepreneurs unhappy with present working conditions: and followers of family tradition role models. The relationship between individuals' motivations and their perceptions of the environment was then investigated. Resources and incentives to start a business were factor- and cluster-analyzed to yield three very different types of perceived environments: munificent environments, characterized by efficient infrastructures, established capital markets and the availability of incentives to start a business: supportive environments, in which the creation of an infrastructure specifically aimed at encouraging new companies could lead to a significant increase in entrepreneurship; sparse environments, lacking both infrastructure and capital availability. The proportions of entrepreneurial types differ significantly in each environment. Government intervention in stimulating the diffusion of entrepreneurship is legitimized by the role new companies play in job and wealth creation and the diffusion of innovation within a territory. These results suggest some implications for public policies: Instead of blanket incentive policies applied on a wide geographical basis, policies tailored on a local basis may be more effective in stimulating new venture creation.